Princípios do movimento de educação do campo: análise dos projetos político-pedagógicos das LEdoC do centro-oeste brasileiro - (:unkn) unknown (Universidade Federal de Goiás, 2018)
The Movement of Field Education after a long process of struggles has pressed the State for the development of projects to build public policies geared to the Education Field, among them the implementation of graduation courses in Field Education (LEdoC), with the purpose of training field educators, having as protagonists the subjects of the field, their experiences, demands and movements. The LEdoC implementation at the universities permeates the construction of Political Pedagogical Project (PPP). So, PPP is an alternative to envision possibilities, ways and strategies to resolve, discuss and materialize issues that are characterized as problems in the educational process, having a decisive role for the implementation of LEdoC on the institution, building spaces for discussion, determining guiding bases, conceptions of word, training, society, and field, as well as social, political, educational, cultural and territorial responsibilities that the teacher major courses and university prioritize. Thus, the aim of this study is to analyze the joints of PPP and the LEdoC with the principles of Field Education Movements. This is a documental research that uses the Content Analysis, following the theory of the Epistemologies of the South and the Decoloniality. It’s analyzed two PPPs of LEdoCs with qualification in Natural Science from Center West of Brazil, which the two universities are: Federal University of Goiás - Catalão Unit and Federal University of Grande Dourados. The punctuated and built principles in this work while constituents of the movement of Field Education are: critical/consciousness Training and overcoming of hegemonic models; Role of Social Movements, Biding with the culture, work and the knowledge of the field; Training for the construction of a field and society project; Training by alternation. According to the analyzes, it’s noted several problems that pervades the PPPs, such as the lack of information about its construction, which brings sings of a construction still based on regulatory innovation, where occurs in an individualize and normative way, from the center to the periphery, away from the collective discussion and articulation with the Social Movements of the Field. It has also noted ideological points that put the PPP as a tool which attempts to appreciate the neutrality, as well as little deepening for political and social debates that surround the Brazilian countryside and the Field Education. However, on this path, in order that the final considerations are still being developed, we noticed potential with positive force. Despite the problems, we see the construction of PPPs that are powerful for the transformation of the University, placing the subjects of the field as protagonists of the process, affirms the importance of the Alternation system, the organization with Social Movements and the importance of looking for peasant’s culture and knowledge. In addition, it has reinforced the need of a critical surveillance on the ideological, political content, intentionality and construction of PPPs, in order that the absences of deepening can give ideas for the use of the PPPs in an ideological distortion perspective, not being powerful to make a Field Education that transforms the reality into a concrete form.
Principles of field rducation’s movement: analysis of political pedagogical projects of LEdoCs in Brazil’s central-western
Keywords: Educação do campo; Movimento de educação do campo; Licenciatura em educação do campo; Field education; Movement of field rducation; Teacher major course in field education; CIENCIAS HUMANAS::EDUCACAO